ANALISIS PENGARUH INDIKATOR KADARZI TERHADAP STATUS GIZI BALITA DI INDONESIA - Riana Pangestu Utami (STIKes CHMK, 2021)
Family conscious nutrition is one of the government program to reduce health and nutrition problem with implementing balance nutrition behavior such as implementing exclusive breastfeeding, monitoring body weight regularly, eating with wide variety of food, consuming iodine fortified salt, and consuming supplementation for family members in need. Stunting is still a major nutrition problem in Indonesia, and implementing family conscious nutrition expected to reducing the problem with family participation. The purpose of this literature review is to find out the effect of implementation family conscious nutrition program on nutritional status and which indicator with greater effect on it. Method used for searching the article with relevant keywords. Program indicator that take effect on height for age nutritional status was breastfeeding practice and eating various food. The support from various party are required to ensure continuity and the success of this program. Keywords: family conscious nutrition, children under five, nutritional status, stunting